Efektivitas Terapi Musik dalam Menurunkan Tekanan Darah pada Pasien dengan Hipertensi - Rifka Hanum; Lestari Sukmarini; Anggri Noorana Zahra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the literature that explores the effectiveness of music therapy in reducing blood pressure in hypertensive patients. The method used is a literature study method using secondary data from previous research which is a journal published from 2018 to 2020 in English and Indonesian journals. The inclusion criteria in this study were: articles explaining music therapy and its benefits in reducing blood pressure, original research, and subjects in this study were patients with hypertension. The types of studies used were randomized controlled trials and quasi-experiments. The literature search used the Clinicalkey, Proquest, Wiley online library, PubMed, and Google Scholar databases. Using the keywords